2017
DOI: 10.1177/1368430217702725
|View full text |Cite
|
Sign up to set email alerts
|

Group-based emotion in group processes and intergroup relations

Abstract: Group-based emotions are experienced as a result of group categorization and group identification. We first review the transformative idea that emotion can occur as a group-level phenomenon driven by group-level processes. We then briefly review the impact of this idea on research about intragroup processes and intergroup relations in the decades since 1998. We conclude by raising some questions whose answers would further extend the reach and predictive power of group-based emotions in both intragroup and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 75 publications
3
43
0
Order By: Relevance
“…Diane Mackie and Eliot Smith (2017) outline their groundbreaking theorizing and research on group-based emotion. Although the advent of multilevel modelling now makes the idea of group-level variance quite unextraordinary, when this theory was first developed it made researchers think differently about what an emotion is.…”
Section: The Anniversary Issuementioning
confidence: 99%
“…Diane Mackie and Eliot Smith (2017) outline their groundbreaking theorizing and research on group-based emotion. Although the advent of multilevel modelling now makes the idea of group-level variance quite unextraordinary, when this theory was first developed it made researchers think differently about what an emotion is.…”
Section: The Anniversary Issuementioning
confidence: 99%
“…However, emotions are time‐dependent responses to environmental cues (Smith & Mackie, ) that predict intergroup outcomes whereas attitudes are typically stable over time and do not predict similar time‐dependent responses to stimuli (Maitner, Mackie, & Smith, ; Prislin, ; Smith & Mackie, ). Previous research has demonstrated the distinct predictive advantage that specific group‐level emotion‐based measures have over group‐level attitude‐based measures for explaining intergroup phenomena (Mackie & Smith, ; Ray, Mackie, Smith & Terman, ; Seger, Banerji, Park, Smith, & Mackie, ), suggesting that meta‐emotions and meta‐attitudes are not interchangeable. Furthermore, we intentionally measured meta‐emotions by assessing perceptions of the outgroup’s specific emotions rather than the general evaluations that meta‐attitudinal measurement would entail (e.g., ‘the outgroup thinks religion is outdated’; Schwarz, ).…”
Section: Discussionmentioning
confidence: 99%
“…We add a racial group cue to our emotions questions to shift and or specify the lens through which the threat is evaluated. Psychology research on emotions suggests, "social categorization into a group changes emotional experience" (Mackie and Smith, 2017). Indeed, Ray et al (2008) found that when a group of students was categorized as Americans, respondents viewed Muslims as threatening and had negative emotions toward them.…”
Section: Methodsmentioning
confidence: 99%